SPE Annual Technical Conference and Exhibition 1992
DOI: 10.2118/24821-ms
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Stability of Proppant in Propped Fractures: Results of a Laboratory Study

Abstract: Factors controlling the stability of proppant in propped fractures were identified and investigated experimentally. The results indicate that the absolute size, distribution and type of proppant may affect stability, and hence the likelihood of proppant flowback. The extent of embedment of the proppant into the rock determined by closure stress and rock hardness) was found to play a key role in stabilising the pack. in addition, channels, which may form due to proppant settling before fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 1 publication
0
31
1
1
Order By: Relevance
“…Formation of a stable pack is easier with softer rock platens which permits deeper particle embedment [15] iii) Presence of softer deformable particles in the pack increases flowback resistance, but will result in loss of porosity and subsequent loss of fluid flow rate [49][50][51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Formation of a stable pack is easier with softer rock platens which permits deeper particle embedment [15] iii) Presence of softer deformable particles in the pack increases flowback resistance, but will result in loss of porosity and subsequent loss of fluid flow rate [49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…Choking is observed while emptying of silos due to the formation of arches. Conversely for the proppants a stable arch has been found to be essential for preventing flowback and maintaining a stable pack [14,15]. Also the linear relation between the filling height and draining time in case of an hourglass filled with fine sand is due to interparticle friction.…”
Section: Granular Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous numerical and experimental investigations of the flowback phenomena concluded that a proppant pack is stable when the range of the ratio of the fracture width to proppant diameter is between the values from three to six. [27][28][29] But these studies did not observe that these ratios are dependent on the cleanup flow rates; on the other hand, the FFCF results 25 show that the proppant flowback can occur within the recommended ratios, albeit at higher fluid rates as compared to the rates for the higher ratios.…”
mentioning
confidence: 88%
“…Such an accumulation process is known to occur in the petroleum industry, where sand is liberated from the host rock during extraction, altering the underground morphology of cracks [5,6]. This may also be relevant for understanding proppant flowback in propped fractures [7]. Additionally, this geometry is representative of a number of recent experimental studies in Hele-Shaw cells [8][9][10][11] where the validity of Janssen stress redirection has not been ascertained.…”
Section: Introductionmentioning
confidence: 99%